PEMBERDAYAAN UMAT LINTAS PAROKI DALAM PENGELOLAAN COLUMBARIUM, KEVIKEPAN DAERAH ISTIMEWA YOGYAKARTA - Karsana, Yusef Widya; Siswanto, Fransiscus Asisi Joko; Anggraini, Fransisca Reni Retno; Rubiyatno, Rubiyatno; Dewi, Novita; Harnoto, L. Bambang (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
This event aims to empower people from various parishes in the management of the Columbarium to be involved in becoming community administrators, awareness of the use of Columbarium facilities, and involvement in praying for the ancestors. There are 2 partners involved in this service, namely Partner 1: Management and Partner 2: Observers and donors. The steps in the dedication are a. inviting people to be involved in novena prayer activities, b. invite people to be involved in the fundraising process, c. invite people to be involved in columbarium development activities and d. invite people to be involved in socializing the use of the columbarium. The result of the dedication is that many people are involved in various activities, namely prayer, raising funds and donors, building activities of the Columbarium, and participating in the socialization of the use of the Columbarium. The Columbarium will be a comfortable, clean, neat, beautiful, cool, safe, orderly storage place for ashes and bones. The facilities available at the Columbarium are: bathrooms, parking lots, seats, tap water, and the Joglo building. The administrators and volunteers are able to maintain and provide services to visitors who will pray for the ancestors.